Development and performance investigation of an inflatable solar drying technology for oyster mushroom - Van Hung, Nguyen; Fuertes, Lei Anne; Balingbing, Carlito; Paulo Roxas, Ampy; Tala, Marvin; Gummert, Martin (MDPI, 2020)
We developed an inflatable solar dryer for mushroom drying, which was adapted from the Solar Bubble DryerTM originally designed for paddy drying. The improved dryer with an added perforated elevated floor ensured the quality without any requirement of mixing or turning of the mushrooms during drying. Its drying performance and economic feasibility were evaluated through determination of the drying parameters including moisture content (MC) reduction, mushroom quality, energy efficiency, greenhouse gas emissions, and cost-benefits ratio. Mushroom MC was reduced from 90% down to 40–60% within 2–4 h, corresponding to the drying rate at this stage of 10–20% h−1. At the next stage, it took about 4–6 h corresponding to a drying rate of 2–10% h−1 to reach the required product MC of 8–10%. The color of the dried mushrooms still remained white-cream. The drying process required 4.57 MJ, emitted 0.33 kg CO2e, and required an input cost of 1.86 $US kg of dry product. For the specific case in the Philippines, this can generate a net profit of 468–1468 $US−1 year−1 and the investment will break even in 1.3–4.0 years corresponding to the selling price of dry mushroom of 10–12 $US kg−1. The study developed a solution to improve the solar bubble dryer and verified its drying process for mushroom drying at farm scale. It would add a significant value to farmers’ income as well as a diversified source of nutrient-rich food.